Trauma Exposure and Domestic Violence Offending Severity in a Probation Sample From Post-conflict Northern Ireland. Issue 3 (February 2022) - Travers, Áine; McDonagh, Tracey; Cunningham, Twylla; Dalsklev, Madeleine; Armour, Cherie; Hansen, Maj
Domestic violence is more common in post-conflict settings such as Northern Ireland. However, the extent to which trauma and related mental health problems are associated with domestic violence perpetration in the region has not yet been quantitatively assessed. The present study examines relationships between multiple traumas, mental health problems, and five indicators of domestic violence perpetration severity (causing injury, use of a weapon, breach of nonmolestation order, sexual violence, and previous police involvement). The unique risk associated with distinct types of trauma (i.e., childhood maltreatment or conflict related) was also investigated. Perpetrators' case file data ( n = 405) were analyzed using hierarchical logistic regression. The rates of recorded trauma exposure and mental health difficulties were 72.3% and 63.5%, respectively. The first logistic regression analyses showed that exposure to multiple traumas was associated with increased likelihood of perpetrating injurious and sexual violence, when controlling for the covariates (odds ratios [ORs] = 1.24–1.28). The second logistic regression analyses showed that childhood maltreatment was the only trauma type to confer unique risk, a relationship that was significant only for the outcome of perpetrating injurious violence (OR = 3.06). Substance misuse was also significantly associated with perpetration of injurious violence, use of weapons, and having past police involvement (ORs = 2.49–3.50). The accumulation of traumatic experiences and substance abuse appear to act as risk factors for some indicators of offending severity. Childhood maltreatment appears to confer particularly strong risk. The findings may support a focus on trauma and substance abuse as intervention targets in post-conflict settings.